Training Larsen Jensen: The return of the great American Miler - Morales, T. (Swimming Technique, 2004)
Larsen Jensen's American record, silver medal performance of 14:45.29 in the 1500 at Athens was the culmination of many months of careful planning and highly-focused training, which is explained in this article.